FLEXIBLE WORKING SPACE, BUDAYA KERJA BARU UNTUK TINGKATKAN PRODUKTIVITAS DAN KINERJA ORGANISASI - Erni Driyantini; Hanisa R Putri Pramukaningtiyas; Yeni Khoirunnisa Agustiani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2020)
Covid-19, which has added more victims than is owned, has resulted in life in general, ranging from social, worship, education, to the world of work. Impact on the world of work is the application of Work From Home (WFH). WFH has become a new work culture or “New Normal” in Indonesia. The Ministry of Finance issued the WFH concept by releasing Flexible Work Space (FWS). Increased productivity and organizational performance are expected from FWS. The application of FWS is a challenge that can increase work-life conflict and increase work pressure. Human Resource Management must support the experience of fairness with a very flexible work relationship, and a more definite resolution is needed to avoid misled employees.